Sistem Appraisal dalam Video Kritik terhadap Kebijakan Pemerintah Daerah - Yunita Ayuningsih; Wawan Gunawan; Budi Hermawan (Journal on Education, 2024)
Social media has become an important means for people to express their opinions and criticisms on various issues, including issues related to local government policies. Criticism towards local governments triggers various interpretations in society. Academics in the field of linguistics should respond to such issues by conducting research, one of which is discourse analysis from the perspective of Systemic Functional Linguistics. The purpose of this research is to reveal how speakers express their attitudes, judgments, and emotions through the language they use to convey criticism towards local government policies. This research employs a qualitative design. The data source is derived from the social media platform, TikTok in the form of videos criticizing local government policies. The result of this research indicate that the aspect of judgment dominates in the transcripts of videos criticizing local government policies followed by appreciation in second place and affect in third place. The most frequently used judgment is personal – negative – criticizing – direct. This aligns with the main objective of the videos criticizing local government policies used as data in this research, which is to criticize or evaluate. After judgment, negative appreciation is the second most prevalent. Lastly, negative affect – direct is the least frequently found in the research data.